The Relationship Between Social Capital and Depressive Symptoms Among the Elderly in China: The Mediating Role of Life Satisfaction - Sun, Jian (Risk Manag Healthc Policy, 2020)
BACKGROUND AND AIM: Depression has become a serious health and social issue in recent years in China. This study aims to explore the relationship between social capital and depressive symptoms among the elderly in China, with a particular focus on the mediating role of life satisfaction. METHODS: The data of this study were sourced from the 2016 wave of China Family Panel Studies (CFPS), involving 1243 older adults aged 60 and above. A multiple linear regression model was used to explore the impact of social capital on depressive symptoms. Moreover, the add-on PROCESS macro for SPSS was employed to measure the mediating effect of life satisfaction on the relationship between social capital and depressive symptoms. RESULTS: The regression results suggest that CES-D score was associated with trust (coefficient = −0.1013, p < 0.01). In addition, the protective role of trust was significantly stronger for older adults aged 70–79, women, the poorest 1/3, and the elderly who live in rural areas. Moreover, the mediation analysis results suggest that the effect of trust on depressive symptoms was fully mediated by life satisfaction. CONCLUSION: This study reveals that social capital has a positive effect on depressive symptoms among the elderly, and the positive health effect shows significant age, gender, income, and location inequalities. Furthermore, this study also provides new evidence indicating that life satisfaction fully mediates the relationship between social capital and depressive symptoms. Improving social capital could be a promising way for China to promote healthy aging in the future.